Health Literacy, 3E 2S Health Behaviors, and Quality of Life among People in Chanthaburi Province - Phattharasirisomboon, Phakwarin; Maneesri, Suwannee; Bunyanuson, Thodsaporn (Journal of Nursing and Public Health Research, 2025)
This cross-sectional study aimed to examine health literacy, 3E 2S health behaviors, quality of life, and factors associated with quality of life among people in Chanthaburi Province. The sample consisted of 400 individuals aged 18 years and older, selected through multistage sampling. Data were collected between August and December 2024. Research instruments included the Health Literacy Questionnaire, the 3E 2S Health Behavior Assessment, and the Thai version of the WHOQOL-BREF questionnaire, with Cronbach’s alpha coefficients of .801, .714, and .862, respectively. The reliability of the health literacy knowledge section was verified using KR-20, yielding a value of 0.76. Data were analyzed using descriptive statistics and stepwise multiple regression analysis. The study revealed that the average health literacy score was at a good level (Mean = 47.81, S.D. = 6.84). The average score for 3E 2S health behaviors was also at a good level (Mean = 22.52, S.D. = 3.67), while the average quality of life score was at a moderate level (Mean = 92.01, S.D. = 12.80). The factors of health literacy (ß = 0.23), 3E 2S health behaviors (ß = 0.16), and age (ß = –0.16) were found to be significant predictors of quality of life among people in Chanthaburi Province, accounting for 12.2% of the variance (R2= 0.12, p-value < 0.05). Therefore, it is recommended that systematic and continuous programs be developed to promote health literacy and 3E 2S health behaviors from an early age in order to improve the quality of life of the population in Chanthaburi Province.